Akuntabilitas Pengelolaan Dana Desa di Desa Benteng Poco Kecamatan Wae Ri’i Kabupaten Manggarai - Yohana Sulistya Ungkur; Alfred O. Ena Mau; Belandina L. Long (Jurnal Ekonomi Manajemen Akuntansi, 2026)
Village Fund management plays a crucial role in promoting local development and community empowerment. However, its implementation often encounters challenges related to limited community participation, insufficient transparency, and the varying effectiveness of government programs. This study aims to analyze the accountability of Village Fund management in Benteng Poco Village, Wae Ri’i District, Manggarai Regency, focusing on three dimensions: process accountability, program accountability, and financial accountability. Employing a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, direct observation, and reviews of official village documents. The findings indicate that process accountability has been implemented adequately through village deliberations and the use of the Siskeudes administrative system, although community understanding and participation remain limited. Program accountability is carried out through regular evaluation meetings, yet the effectiveness of several programs is hampered by insufficient technical support and lack of sustainability. Financial accountability demonstrates a commitment to transparency, particularly through the publication of budget information, although the presentation of financial data remains difficult for some villagers to fully understand. This study highlights the need to enhance community involvement, simplify public financial information, and strengthen program support mechanisms to achieve transparent and accountable Village Fund governance.